Direct Imaging of Octahedral Distortion in a Complex Molybdenum Vanadium Mixed Oxide1. (27th April 2015) - Lunkenbein, Thomas; Girgsdies, Frank; Wernbacher, Anna; Noack, Johannes; Auffermann, Gudrun; Yasuhara, Akira; Klein‐Hoffmann, Achim; Ueda, Wataru; Eichelbaum, Maik; Trunschke, Annette; Schlögl, Robert; Willinger, Marc G.
Abstract: Complex Mo, V‐based mixed oxides that crystallize in the orthorhombic M1‐type structure are promising candidates for the selective oxidation of small alkanes. The oxygen sublattice of such a complex oxide has been studied by annular bright field scanning transmission electron microscopy. The recorded micrographs directly display the local distortion in the metal oxygen octahedra. From the degree of distortion we are able to draw conclusions on the distribution of oxidation states in the cation columns at different sites. The results are supported by X‐ray diffraction and electron paramagnetic resonance measurements that provide integral details about the crystal structure and spin coupling, respectively.